Strategi Guru dalam Mengelola Kelas Pada Mata Pelajaran Matematika Kelas IV MI NW Keruak - Irwan Yon Hadi (Pendidikan Al-Gafari, 2024)
A strategy is a plan that contains a series of activities designed to achieve educational goals. The problem in this research is that students don’t like mathematics lessons because they are considered boring and some of the reasons why students don’t like calculations are because mathematics lessons are considered too difficult, complicated, draining their minds, and also boring. That above can be understood especially if when learning mathematics the material is presented in a super serious way. This research aims to determine teacher strategies, factors inhibiting the implementation of teacher strategies, and their solutions at MI NW Keruak. The type of research used is descriptive qualitative research, data is obtained by observing, interviewing, and documenting. The validity of the researcher's data uses triangulation techniques. Data analysis was carried out in four stages: data collection, data reduction, data presentation, and conclusion. The results of this research show that classroom management is an effort made by teachers to help create optimal conditions. Classroom management is the art or practice of work where the teacher works individually with or through other people to optimize class resources for the creation of an effective and efficient learning process, as well as effective singing methods and squad game methods carried out by a teacher so that mathematics learning is not boring.